Time for Change - Maggie Hartnett; Alison Fields (Flexible Learning Association of New Zealand, 2022)
Associate Editor Maggie Hartnett says farewell while casting an eye over the achievements of the Journal of Open, Flexible and Distance Learning in the past 8 years. This issue presents four articles providing a rounded view of managing and improving emergency remote teaching (ERT) in the context of the COVID-19 pandemic. The first two articles focus on the experience of teachers in ERT; one provides empirical research; and one is a position piece on the uptake and value of learning management systems (LMSs) for delivering this remote teaching. These practical and timely articles provide research and thought of substance as the pandemic continues.